The representation of female journalists and the female voice in the South African newspapers: a case study of the Cape Times - Graff, Lara A B (Centre for Film and Media Studies, 2017)
Over the past 15 years, there has been limited research regarding gender and journalism in a South African context. Existing research implies that there is almost complete gender balance across all media. Yet, despite the gender parity in the workforce, women are underrepresented in senior and key decision-making positions, indicating that a glass ceiling still exists for female journalists in South Africa. Furthermore, newsrooms are still dominated by patriarchal practices, norms and values. This study investigated the representation of female journalists in South African daily newspapers via one case study: the Cape Times. It shed light on what type of stories female journalists report on in comparison to their male colleagues and identified patterns in female reporting. The study also investigated how transformative policies may have affected newsrooms. Further, attention was paid to the female voice in the print media in terms of the use of female sources and women as the subject of news stories. The data for this study was generated through a content analysis and interview research. The content analysis was conducted on articles of the Cape Times newspaper and was based on three research questions regarding representation, female voice in the media and topic assignment/ contribution. As part of the interview research, in-depth informant interviews were conducted with female journalists and editors; the aim was to collect industry insight and opinions regarding the representation of female journalists and female voices in South African newspapers. The study revealed that the assignment of stories has been characterised by constant fluctuations over the past 20 years. It became apparent that effort is put into gender balance not only when it comes to the representation of journalists, but also the assignment of beats. However, the study indicated a significant difference between the representation of female journalists and the female voice in the print media. It also highlighted issues of gender inequality in reporting. The study revealed that while South Africa's newsrooms might be progressing towards gender balance, patriarchal structures and views are still embedded in the print media. These findings are congruent with the existing academic literature. This research further revealed that structures and issues of the newsroom or the media reflect issues and structures of South African society. Past research in a South African context has been very limited, making this study one of a few of its kind and its findings are indicative for other print media, filling a gap in the literature.